ORIENTASI NILAI NAHDLATUL ULAMA DALAM KEHIDUPAN SOSIAL MASYARAKAT DI KOTA MANADO - M. Agung Naser (HOLISTIK, Journal of Social and Culture, 2023)
Islamic organizations in Indonesia are an interesting phenomenon to study, considering that Islamic organizations are representatives of Muslims who are the majority in Indonesia, Nahdlatul Ulama also views plurality as a necessity (sunnatullah), providing guarantees and tolerance in maintaining common relations by laying down universal values, such as the principles of justice, togetherness and honesty. Radicalism and religion-based hate speech in Indonesia in several religious practices often trigger various conflicts, conflicts, and disputes. This is a real threat to the security and integrity of life of the nation and state based on the ideology of Pancasila. Therefore, preventing, counteracting and being aware of the threat of the spread of radicalism is not only the role of the security forces but requires the role and support and participation of the community and socio-religious organizations. This further shows that religious freedom is still a crucial problem for social life in Indonesia and can be a threat to the harmony of life of the people in Manado City The value of Nahdlatul Ulama in the social life of the community in Manado City is very visible as a medium of glue for social relations or Ukhuwah Islamiyah to community members, in addition to showing the strengthening of religious rituals in each individual in finding their identity and efforts to get closer to their god, while in the social dimension it can be a guide for achieving collective ideals both social and cultural. Keywords: value, Nahdlatul Ulama, social life